Metafory potoczne a kompetencja komunikacyjna osób niesłyszących (Conversatoria Linguistica, 2019)
Metaphors are so profoundly prevalent in human life that very often we do notrealize their existence. This lack of the awareness is the reason why we tend touse certain expressions and phrases containing metaphors without a flick.Some metaphoric expressions have rooted so deeply in our language traditionand have become so popular and widespread that it does not pose any problemfor us to comprehend them. In the view of that it is very challenging andthough provoking to establish if the deaf are capable of processing and understandingcommon metaphors as well. Can the metaphoric expressions befound in the conceptual framework of the hearing-impaired person? Whatwould be the way to perceive and interpret such expressions?